Pengaruh Pengetahuan Kewirausahaan dan Ekspektasi Pendapatan terhadap Minat Berwirausaha pada Mahasiswa Jurusan Akuntansi dan Administrasi Niaga Politeknik Negeri Ujung Pandang - Usman, Ahmadi; Roesly, Lismaya (Journal of Business Administration (JBA), 2025)
This research aimed to examine the influence of entrepreneurial knowledge and income expectations on entrepreneurship intention among students in the Department of Accounting & Business Administration at State Polytechnic of Ujung Pandang. The population of this research consisted of 468 respondents selected. The sample consisted of 267 students from the Department of Accounting and Business Administration who had taken entrepreneurship courses used purposive sampling and stratified random sampling techniques. Data collection was conducted through questionnaires and interviews. Data analysis included instrument validation, descriptive statistics and inferential statistics. The data were analyzed used SPSS version 25 software. The results of this research indicate that 1) the perception of students regarding the entrepreneurial knowledge for entrepreneurship was highly favorable, 2) the perception of students regarding income expectations in entrepreneurship was notably high, 3) the perception of students regarding entrepreneurship intention was highly interested, 4) entrepreneurial knowledge had a positive and significant effect on entrepreneurship intention among students, 5) income expectations had a positive and significant effect on entrepreneurship intention among students, 6) entrepreneurial knowledge and income expectations had a positive and significant effect on entrepreneurship intention among students. Furthermore, the coefficient of determination of this research was 0.581. This means that the variables of entrepreneurial knowledge and income expectations contribute 58.1% to entrepreneurship intention, while the remaining 41.9% was explained by other variables outside of this research.